2007
DOI: 10.1624/105812407x217110
|View full text |Cite
|
Sign up to set email alerts
|

Care Practice #3: Continuous Labor Support

Abstract: This updated edition of Care Practice Paper #3 presents the evidence for the benefits of continuous support in labor. The role of the doula is explained. Women are encouraged to plan for continuous support during labor and to consider including a woman experienced with childbirth among their labor support team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 3 publications
0
11
0
5
Order By: Relevance
“…The presence of family members during child birth experiences has been recommended by WHO as one of the main aspects of humanized care [33]. The benefits of continuous one-on-one support by a companion during labor have also been noted by a Cochrane systematic review [34], and other research reviews in the past [35,36]. The presence of a companion or family members in the ICU or operating rooms has also been shown to provide positive psychological support for the pregnant women, whilst the care providers concentrate on the task of attending to more medical issues during the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of family members during child birth experiences has been recommended by WHO as one of the main aspects of humanized care [33]. The benefits of continuous one-on-one support by a companion during labor have also been noted by a Cochrane systematic review [34], and other research reviews in the past [35,36]. The presence of a companion or family members in the ICU or operating rooms has also been shown to provide positive psychological support for the pregnant women, whilst the care providers concentrate on the task of attending to more medical issues during the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Many definitions of the doula role also encompass informational support and advocacy . Informational support may be described as explaining, answering questions, or giving ‘information about what's happening during labour’ as well as bringing the doula into the process of preparing for informed choice by discussing ‘options, risks and benefits of the different approaches available in maternity care’ . The definition of advocacy is more contested.…”
Section: What Is a Doula?mentioning
confidence: 99%
“…One approach views advocacy on the doula's part as a way to support the client in voicing her own intentions and increase her involvement in decision‐making. This approach often emphasizes that doulas do not give advice (especially medical advice) and do not speak for their clients, but may identify questions the client may ask and help her communicate on her own behalf with medical staff . Another approach, offered primarily by academic articles and consumer materials, places the doula‐as‐advocate in an intermediary role, ‘communicating and interpreting the mother's desires to care providers during labour’, ‘question[ing] a clinical intervention at the behest of the mother’, giving ‘advice’, or ‘add[ing] another opinion to the mix when decisions need to be made regarding the management of … labor’…”
Section: What Is a Doula?mentioning
confidence: 99%
“…This support is most likely to be taken for granted in Western societies, because this is an enjoyable occasion, and the father typically wants to participate during birth and provide support to the woman. 16 A recent review, however, reported that men often perceived a lack of ability to provide support. 17 Women's perceptions of control during birth and its association with the birth experience has been extensively investigated.…”
mentioning
confidence: 99%